Peristenotic Collateral Circulation in Atherosclerotic Renovascular Disease: Association With Kidney Function and Response to Treatment. Issue 2 (August 2020) - Afarideh, Mohsen; Zhang, Xin; Ferguson, Christopher M.; Glockner, James F.; Lerman, Amir; Textor, Stephen C.; Lerman, Lilach O.
Abstract : The significance of peristenotic collateral circulation (PCC) development around a stenotic renal artery is unknown. We tested the hypothesis that PCC is linked to loss of kidney function and recovery potential in patients with atherosclerotic renovascular disease (ARVD). Thirty-four patients with ARVD were assigned to medical-therapy with or without revascularization based on clinical indications. The PCC was visualized using multidetector computed tomography and defined relative to segmental arteries in patients with essential hypertension. PCC number before and 3 months after treatment was correlated with various renal parameters. Thirty-four stenotic kidneys from 30 patients were analyzed. PCC number correlated inversely with kidney volume. ARVD–stenotic kidneys with baseline PCC (collateral ARVD [C-ARVD], n=13) associated with elevated 24-hour urine protein and stenotic kidney vein level of tumor necrosis factor-α, lower single-kidney volume and blood flow, and greater hypoxia than in stenotic kidneys with no PCC (no collateral ARVD [NC-ARVD], n=17). Revascularization (but not medical-therapy alone) improved stenotic kidney function and reduced inflammation in both NC-ARVD and C-ARVD. In C-ARVD, revascularization also increased stenotic kidney volume, blood flow, and oxygenation to levels comparable to NC-ARVD, and induced PCC regression. However, revascularization improved systolic blood pressure, plasma renin activity, and filtration fraction only in NC-ARVD. Therefore, patients with C-ARVD have greater kidney dysfunction, atrophy, hypoxia, and inflammation compared with patients with NC-ARVD, suggesting that PCC does not effectively protect the stenotic kidney in ARVD. Renal artery revascularization improved in C-ARVD stenotic kidney function, but not hypertension or renin-angiotensin system activation. These observations may help direct management of patients with ARVD. Abstract : Supplemental Digital Content is available in the text.